An Appraisal of Delinquent Behaviours among Secondary School Students in Ondo State, Nigeria - Tayo-Olajubutu, Olufunmilayo (Advances in Social Sciences Research Journal, 2017)
The study was designed to appraise delinquent behaviours among secondary school students in Akure North and Akure South Local Government Areas of Ondo State, Nigeria. Two hundred students of senior secondary classes two and three (SS2 and SS3), were used as sample. Two of the selected schools were mixed, while the other two were girls’ and boys’ only respectively. The research instrument for the study was a self-constructed questionnaire entitled “Appraisal of Delinquent Behaviour Questionnaire (ADBQ)” Data collected were analyzed using percentage (%). Findings from the study showed that the parent, the teacher and the media, are all instrumental to students’ delinquent behaviours. Based on the findings of the study, conclusion was drawn and recommendations made.